Ultracentrifugation method for exosome isolation of HEK293 cells as a candidate model in-vitro therapy of breast cancer - RIZKI NOVA AMELIDA; SILMI MARIYA; BELLA FATIMA DORA ZAELANI; YULIANA YULIANA; HEPY DAYANA; HUDA S. DARUSMAN (Society for Indonesian Biodiversity, 2023)
Abstract. Amelida RN, Mariya S, Zaelani BFD, Yuliana, Dayana H, Darusman HS. 2023. Ultracentrifugation method for exosome isolation of HEK293 cells as a candidate model in-vitro therapy of breast cancer. Biodiversitas 24: 5074-5079. Exosomes are secreted by all cells and found in all body fluids, providing the biological system. They have great potential in cancer immunotherapy and have different roles and targets. The biological function of an exosome relies on its bioactive activities, supported by lipids, proteins, and nucleic acids. Exosomes can be isolated by the ultracentrifugation method, widely used to produce exosomes from various sources and intended to pellet containing heterogeneous particles and the exosomes. In this study, we isolated exosomes derived from HEK293 cells using the ultracentrifugation method and applied directly in vitro to MCF-7 cells. The exosomes were added to the MCF-7 cells at various concentrations, 3,5 µg/mL, 7 µg/mL, and 14 µg/mL, evaluated using P53 and PCNA markers. The study showed that the exosomes had been successfully isolated; the concentration obtained was 24,95 µg/mL and expressed exosome markers CD9 and CD81. The MCF-7 cells were treated by exosome and demonstrated epithelial-like morphology. The cell population survived, but the confluency decreased at higher concentrations, as did viability. The marker of P53 and PCNA expression resulted from the effect of exosome treatment. The results indicate that the exosome can potentially inhibit the growth of breast cancer cells in vitro.